Educational approaches to teach students to address colonialism in global health: a scoping review - Anna Kalbarczyk; Holly Nishimura; Sylvie Perkins; Praise F Olatunde (BMJ Global Health)
Introduction The enduring legacy of colonisation on global health education, research and practice is receiving increased attention and has led to calls for the ‘decolonisation of global health’. There is little evidence on effective educational approaches to teach students to critically examine and dismantle structures that perpetuate colonial legacies and neocolonialist control that influence in global health.Methods We conducted a scoping review of the published literature to provide a synthesis of guidelines for, and evaluations of educational approaches focused on anticolonial education in global health. We searched five databases using terms generated to capture three concepts, ‘global health’, ‘education’ and ‘colonialism’. Pairs of study team members conducted each step of the review, following Preferred Reporting Items for Systematic reviews and Meta-Analyse guidelines; any conflicts were resolved by a third reviewer.Results This search retrieved 1153 unique references; 28 articles were included in the final analysis. The articles centred North American students; their training, their evaluations of educational experiences, their individual awareness and their experiential learning. Few references discussed pedagogical approaches or education theory in guidelines and descriptions of educational approaches. There was limited emphasis on alternative ways of knowing, prioritisation of partners’ experiences, and affecting systemic change.Conclusion Explicit incorporation of anticolonial curricula in global health education, informed by antioppressive pedagogy and meaningful collaboration with Indigenous and low-income and middle-income country partners, is needed in both classroom and global health learning experiences.